Pusat Wisata Kuliner Di Siak Dengan Pendekatan Arsitektur Neo Vernakular - Maya Purnamasari; Yohannes Firzal; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Siak Regency is located in Riau Province and is included in the Riau tourism development area and seeks to develop tourism by increasing events and tourist attractions that can be visited by the publicor tourists. Tourists are always closely related to culinary to taste food and drinks typical of tourist destinations. Currently, culinary places in Siak have not been realized properly because they do notmeet architectural standards. In addition Siak tourism also presents cultural and historical tourism experiences in the form of Malay Siak houses and efforts are needed to introduce them to tourists. Soit takes a container and renewal in the form of a culinary tourism center design in Siak with the theme of neo vernacular architecture. The research methods used include field data collection, literaturestudies and empirical studies. The results of this study are in the form of a culinary tourism center design by applying the concept of court based on the functions and themes of the building. Theconcept of building applied to the building is the way the building's mass order and the oblique shape on the outside of the building's side, while the application of the theme is taken the most prominentcharacteristic part of the Siak Malay house. The elements applied are the form of a pyramid roof that extends to the back, utilizing openings as natural lighting and ventilation, using the platform as anentrance. stage form, and ornament.Keywords: culinary tourism center, architecture, neo vernacular